Education for Sustainable Development (ESD) Research Trends 2020-2024: Bibliometrics Analysis - Luthfiyah, Ana; Subroto, Waspodo Tjipto; Sakti, Norida Canda (IKIP PGRI Bojonegoro, 2025)
This study examines Education for Sustainable Development (ESD) research trends from 2020 to 2024 using bibliometric analysis with Scopus data and VOSviewer. It identifies key keywords, author collaborations, and influential journals or institutions in ESD. The findings reveal a significant rise in ESD publications, with European countries like Spain, Germany, and Sweden leading contributions. Cross-country and interdisciplinary collaborations enrich the ESD literature and promote integrative approaches in education. Bibliometric visualizations highlight interconnected themes such as higher education, teacher training, and sustainability policy. Stakeholder engagement and experiential learning are identified as crucial for ESD implementation. This research provides valuable insights into ESD's development and offers recommendations to enhance its effectiveness in advancing sustainability goals across educational levels.